ACUTE CHOLECYSTITIS CAUSED BY GRANULOMATOSIS WITH POLYANGIITIS - A RARE CASE - Petković, Vanja; Golubović, Sonja; Ilić, Tatjana; Jelčić, Sandra; Ostojić, Zorana; Knežević, Violeta (Medicinski časopis, 2025)
The most commonly affected organs in Granulomatosis with polyangiitis (GPA) include kidneys and lungs, while presentation in other organ systems is rare. [1, 2, 3]. We hereby present a case of vasculitic changes in the gallbladder, as the initial manifestation of GPA. A 65-year-old woman presented with fever and generalized weakness and was admitted to hospital. Upon admission, physical examination revealed signs of dehydration, mild hypotension and tachycardia. There was no palpable tenderness in the abdomen, and Murphy’s sign was negative. Initial work-up revealed normocytic anemia, elevated markers of inflammation. Urinalysis revealed protein and red blood cells. Blood and urine cultures were negative, and no signs of inflammation were identified on radiographic imaging. Due to persisting fever and unresolved inflammatory process despite the usage of parenteral antibiotic treatment, a computed tomography (CT) was also performed and revealed calculous cholecystitis necessitating laparoscopic cholecystectomy. Histopathology of the resected gallbladder showed small-vessel vasculitis. Laboratory tests revealed positive proteinase-3-anti-neutrophil cytoplasmic antibodies (PR3-ANCA) with an onset of renal dysfunction. These results supported a diagnosis of granulomatosis with polyangiitis (GPA) and the patient was started with glucocorticoids and intravenous cyclophosphamide. After this treatment, the patient’s general condition stabilized, creatinine and C-reactive protein levels decreased, and anemia resolved as well. This case highlights the importance of considering vasculitis in patients with unexplained persistent fever and systemic symptoms, especially when common causes have been excluded.
Keywords: ANCA vasculitis, žučna kesa, PR3